Consumption Values and Destination Evaluation in Destination Decision Making - Vasyl Denys; Júlio Mendes (Journal of Spatial and Organizational Dynamics, 2014)
Consumption values have received little attention in the tourism literature, comparing to such determinants of the consumer behavior as motivations, pull and push factors, satisfaction, quality, or destination image, etc. This study attempts to analyze consumption values and their types, and the influence that they have on the destination decision making and, particularly, on the destination choice. Current work brings new insights about the role of consumption values in detrmining preferences toward tourist destinations. Study findings justify the multidimensional nature of the consumption value, and demonstrate that every value dimension has a certain degree of importance for a tourist, which, to a big extent, can determine the destination choice.